PENDAMPINGAN BACA TULIS Al-QURAN UNTUK MENINGKATKAN KELANCARAN DI TKA/TPA NURUL IKHSAN DESA SUKA DAMAI KECAMATAN TELUK PANDAN - Putri Belawati Pandiangan, Anjani; Kadir, H.Abdul; Setiawati, Putri; Rosidin, Ahyar; Qairimatun Ain, Juliya; Ali Ridho, Mahrus; Ihtisor Hizbi, Muhammad; Yuliana, Yuliana; Athdilla Insira, Rieysha (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2024)
Assistance in reading and writing the Koran at TKA/TPA level is very important for children at an early age. So it can improve the fluency of reading Hijaiyah letters. The mentoring method provided to TKA/TPA Nurul Ikhsan Suka Damai Village students is to observe how far the students understand and master the Al-Quran. The research results showed that there was a significant increase in the ability to read and write the Al-Quran in students who took special assistance. This research underlines the importance of effective mentoring methods in improving Al-Qur'an reading and writing skills at the TKA/TPA level. The results of observations show that children in Suka Damai village have not yet mastered the ability to pronounce and memorize letters properly and correctly. The implications of this research can be the basis for developing similar programs in other educational institutions with the aim of increasing Al-Qur'an literacy among young children. Therefore, we help provide assistance in reading and writing the Koran through the Iqra method. The iqra method is a method of learning the Al-Qur'an using the iqra book guide.